?Effect of Video Assisted Teaching on Prevention and Management of Dengue among Mothers in a Selected Rural Community, Kancheepuram District, Tamil Nadu, India (Medico Legal Update, 2020)
Dengue is one of the most common mosquito borne diseases in India and it is most prevalent condition in thecommunity. The number of cases of dengue goes up high during monsoon season as the mosquito breed instagnant water and in warm and humid weather. The study topic was “Effects of video assisted teaching onprevention and management of dengue among mothers in selected rural community, Kanchipuram District,Tamil Nadu, India”. The objectives of the study were to assess the pre and post-test knowledge of mothersregarding prevention and management of dengue, to assess the effectiveness on video assisted teachingamong the mothers in the rural community and to find out the association between pre-test knowledgescores regarding prevention and management of dengue with selected demographic variable. Quantitativeresearch approach was used for this study. Quasi-experimental, one group pre-test post-test design wasused for this study. The sample consists of 194 mothers. Self structure questionnaire was used to assessthe effect on video assisted teaching on prevention and management of dengue. The data collection periodwas one week. The data was collected in 194 mothers in the age group between 20 to 60 years in pooncherirural community. The samples are selected by using simple random sampling technique. The data wasanalyzed and tabulated. The results shows pre-test knowledge scores on prevention and management ondengue was 51% (98) had moderate knowledge, 43% (84) had inadequate, 6%(12) had adequate knowledge.Post-test knowledge scores after video assisted teaching on prevention and management on dengue was9%(18) had moderate knowledge and 91% (176) had adequate knowledge. Study shows that there wassignificant association between pre-test and post-test knowledge of mothers with T Value of 25.76 whichwas statistically significant at p